IMPROVING THE MANAGEMENT EFFICIENCY OF THE HIGHER EDUCATION INSTITUTION THROUGH ECONOMIC DIAGNOSTICS - Jo‘rayev Soxibjon Nodirbek o‘g‘li (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
The article describes the role of economic diagnostics in ensuring the effectiveness of higher education institutions and the importance of diagnostic principles in management. A scientific conclusion and practical recommendations related to the economic evaluation of higher education activities are given.